2019
DOI: 10.3390/insects10090301
|View full text |Cite
|
Sign up to set email alerts
|

Hemocyte Changes During Immune Melanization in Bombyx Mori Infected with Escherichia coli

Abstract: Hemolymph melanization is a conserved immune response in insects and other arthropods. However, the physiological process of the hemolymph system in the melanization response is hardly studied. Here, alterations of hemocytes in immune melanization were observed by Escherichia coli infection in Bombyx mori. Results first showed that there were cells aggregating into clusters. However, it vanished, and only part of clustered hemocytes were melanized during the period of intense immunity. The hemocyte numbers imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 49 publications
(56 reference statements)
3
16
0
Order By: Relevance
“…The stimulation or modulation of immune cells occurs very rapidly, and this is the reason we conducted the experiments for nine days. This study is in line with other studies that had revealed that, due to bacterial infection, the hemocyte levels in invertebrates change within hours [39,40]. The cellular immune response was triggered within minutes of bacterial introduction, and the time required for the bacterial immune challenges can be seen in a hemocyte and phagocytosis assay is 24 h [41].…”
Section: Discussionsupporting
confidence: 91%
“…The stimulation or modulation of immune cells occurs very rapidly, and this is the reason we conducted the experiments for nine days. This study is in line with other studies that had revealed that, due to bacterial infection, the hemocyte levels in invertebrates change within hours [39,40]. The cellular immune response was triggered within minutes of bacterial introduction, and the time required for the bacterial immune challenges can be seen in a hemocyte and phagocytosis assay is 24 h [41].…”
Section: Discussionsupporting
confidence: 91%
“…The gradual increase in the number of hemocytes circulating in the hemolymph of larvae, pupae and adult insects observed in the course of the study may not only be the result of differences in the half-life of the peptides in the insect hemolymph but may also indicate a gradual release of tissue-settled hemocytes as well as new populations of these cells from the hematopoietic organs. Restoration of the number of hemocytes in insect hemolymph was also found in Bombyx mori larvae after Escherichia coli injections 53 . Recently, we showed a similar effect in T. molitor individuals injected with either a solution of another immunomodulatory insect peptide, alloferon, or one of its analogs.…”
Section: Discussionmentioning
confidence: 72%
“…This, in turn, may explain the strong melanization response against P. larvae observed in the present study. Nodulation is the deposition of melanin in the formed nodules on the surface of encapsulated antigens and in hemolymph clots at the wound vicinity in insects ( Koella and Sørensen, 2002 , Li et al, 2019 ). The current study showed strong nodulation responses as early as 4 h and peaked 48 h post- P. larvae injection.…”
Section: Discussionmentioning
confidence: 99%